Stability of thin-film CdTe solar cells with various back contacts - Hill, Taylor D., author; Sites, James, advisor; Sampath, Walajabad, advisor; Bradley, Mark, committee member (Colorado State University. Libraries, 2021)
With an increasing reliance on photovoltaic energy comes an ever-increasing demand to understand the mechanisms of failure which lead one to having an under-performing solar module. Recent technological advances have proven CdTe solar cells to be competitive with traditional Si, taking up 5% of the world solar market and reaching efficiency upwards of 22.1% for small area scale and 18.6% for module scale. This thesis explores various back-contact configurations to reduce the contact barrier height as well as how they hold up under accelerated lifetime testing. Various degradation mechanisms, such as diffusion of species, drift within the built-in fields, and formations of various impurities/complexes on the surface and within the bulk were explored. The results of accelerated-lifetime experiments revealed the instability of devices with large amounts of Cu and those containing the colloidal Ni based paint solution as a metallic back contact. Sputtered films of nickel doped with vanadium (Ni:V) and chromium (Cr) demonstrated the capability to produce cells with efficiencies between 12-13% with fill factors up to 75%. Metallic bilayers containing a metallic cap of aluminum (Al) were then evaluated, demonstrating an increase in efficiency up to 15.1%. Buffer layers of NiO revealed the presence of a large back-contact barrier via the rollover effect in forward bias, leading to devices with efficiency of only 3%, but subsequent work revealed that by applying the NiO buffer prior to CdCl2 passivation reduces the back barrier and produces cells with peak efficiency of 14.8%.
Keywords: stability; CdTe; thin-films